Guided transtracheal distal pulmonary brushing-washing: diagnosing acute pneumonia in high-risk patients. - Peltier, P (1982)
Transtracheal brushing-washing of distal pulmonary lesions was performed in 20 patients. Specimens were obtained by brushing and washing through a catheter placed in the pulmonary lesion with the aid of a guide. In nine patients pathogenic organisms were isolated. In the other 11 patients infectious studies of the specimens were negative, five of the patients (true-negatives) showing no infection and six (false-negatives) showing infection. Serious complications were uncommon, but one patient, who had diffuse intravascular coagulation, died. This procedure seems to represent an advance over transtracheal aspiration and is an effective alternative to such invasive methods are transthoracic lung aspiration and pulmonary biopsy.